A cross-sectional study on the prevalence of multidrug-resistant clinical isolates of Proteus species in Northern Iran - Mahnaz Shafaei Fallah; Hadi Razavi Nikoo; Aylar Jamali; Alireza Mohebbi; Ezzat Allah Ghaemi (Journal of Infection in Developing Countries)
Introduction: Multidrug-resistant (MDR) bacteria like Proteus species have led to more prolonged hospitalizations, fewer care choices, higher treatment costs, and even death. The present study aims to evaluate the prevalence of MDR Proteus species in clinical samples and to suggest the best therapeutic options for the MDR Proteus species.